PENGEMBANGAN KURIKULUM KEWIRAUSAHAAN MENGGUNAKAN E-COMMERCE DALAM MENINGKATKAN NIAT WIRAUSAHA SISWA SMA NEGERI KOTA SURAKARTA - Bambang Triyono (LP2M IAIN Tulungagung, 2018)
The aims of this study are; (1) Generate the required learning and entrepreneurial craft lessons vocational high schools in Surakarta; (2) Develop information systems and e-commerce technology as a learning tool craft and vocational secondary school entrepreneurship in Surakarta; (3) Test try information system and e-commerce technology as a learning tool and entrepreneurial craft is applied in vocational high schools in Surakarta. (4) Knowing intention student after using information systems and e-commerce technology as a learning tool craft and vocational secondary school entrepreneurship in Surakarta. This study uses research and development methodology. The population of the study is teachers entrepreneurship craft and Vocational High School students in Surakarta. The data analysis technique used in this study is Structural Equation Modeling (SEM). The sampling of this study used was the quota. To meet the assumptions of sample adequacy in SEM analysis, the sample size in this study is 125 respndens. Keywords: E-Commerce, The Craft, Entrepreneurial Learning